Absorbance Characteristics of Chlorophyll Extracts of Spinach (Amaranthus Hybridus & Amaranthus tricolor) and Water spinach (Ipomea spp.) as Sensitizers - Iqbal, Iqbal; Basri, Zainuddin; Adyatma, Abyudan; Khaeroni, Rany; Darwis, Darmawati (Journal of the Physical Society of Indonesia, 2025)
The development of dyes has moved from natural sources, such as minerals, plants, and animals, to synthetic substitutes since the discovery of mauveine in 1856. The industrial revolution has changed the way dyes are made and sparked environmental concerns, which has led to a renewed interest in natural colors for food, cosmetics, and textiles. In dye-sensitized solar cells (DSSCs), the potential of chlorophyll extracts from water spinach (Ipomoea spp.) and spinach (Amaranthus tricolor) as long-lasting photosensitizers is investigated in this work. Amaranthus tricolor has a high total chlorophyll content of 10.367 mg/g, which is made up of 9.551 mg/g of chlorophyll and 0.818 mg/g of chlorophyll b, according to a chlorophyll content analysis. Significant amounts of chlorophyll were also present in Amaranthus hybridus, which had 10.462 mg/g (9.181 mg/g of chlorophyll and 1.283 mg/g of chlorophyll b). Ipomoea species, on the other hand, had a lower chlorophyll concentration (5.380 mg/g). Significant absorption peaks were found in the 380–460 nm range by acetone extraction and UV–Vis spectrophotometry, highlighting the significance of efficient light absorption for photosynthesis. Amaranthus tricolor is a very ideal plant for distributed solar power system applications due to its exceptional light energy conversion performance. But during storage, environmental stressors including senescence and light intensity caused chlorophyll to degrade, which shifted the absorbance maxima to shorter wavelengths and decreased the efficiency of light absorption. Amaranthus tricolor, in spite of this, continues to be a viable option for environmentally benign natural chlorophyll alternatives for industrial and renewable energy applications.